Analysis of Wireless Power Transfer between Near-Field Antennas Using the Bi-Characteristic-Impedance Transmission Line (BCITL) Model - Phaebua, Kittisak; Phongcharoenpanich, Chuwong; Lertwiriyaprapa, Titipong; Torrungrueng, Danai; Chou, Hsi Tseng (My University, 2025)
Analysis of wireless power transfer (WPT) between near-field (NF) antennas is proposed by using a bi-characteristic- impedance transmission line (BCITL) model. In particular, misalignment between small NF transmitting (TX) and receiving (RX) antennas degrades the power transfer efficiency (PTE). The proposed novel optimization procedure, based on the BCITL model, effectively maximizes WPT area, which is strongly influenced by antenna characteristics, the RX antenna's position, and the load reflection coefficient (ΓL) at each misaligned position. In such misalignment, ΓL ≠ 0, which is a crucial parameter in impedance matching to broaden the WPT area. This letter investigates the ΓL impact on the PTE at misaligned positions based on BCITL parameters, providing a new optimization framework that adapts to varying degrees of misalignment. In simulation and measurement validation, it is demonstrated that this BCITL model may estimate an optimal ΓL (ΓL ≠ 0) to produce WPT areas much broader than those using the conventional matching condition (ΓL = 0).
Keywords: Antenna matching circuit; bi-characteristic-impedance; near-field communication; wireless power transfer (WPT)